PENERAPAN MANAJEMEN MUTU BERBASIS ISO 9001 : 2015 : RSUD DR. Sam Ratulangi Tondano - Rey Lensun; Shirly S. Lumeno; Yessy C.S Pandeiroth, (Sustainable Construction (SUSCON), 2024)
In the construction industry, ISO 9001:2015 certification is the primary choice for contractors aiming to implement a consistent and systematic quality management system. This certification serves as tangible proof that a company has adopted quality management practices in all its activities, recognized both nationally and internationally. However, its implementation faces various challenges, including the readiness of human resources, document preparation and verification, as well as the commitment of leadership and employees. In North Sulawesi Province, the implementation of quality management system standards is still insufficiently addressed due to issues such as traditional organizational structures, a lack of skilled human resources, work culture, technology mastery, and short-term planning. This situation provides opportunities for national and out-of-region contractors to undertake large-scale projects there. The implementation of the ISO 9001:2015 quality management system in the Sam Ratulangi Hospital construction project in Tondano emphasizes several critical factors: risk-based thinking, organizational management documentation, SOP establishment, information system organization, and leadership commitment. The main obstacles in implementing ISO 9001:2015 include the low understanding of construction human resources on the importance of quality implementation, insufficient government support for skill enhancement, the need for organizational system reorganization, and the lack of owned equipment. This research concludes that improvements from contractors and support from local governments are necessary to encourage the implementation of the ISO 9001:2015-based quality management system. This will increase the construction business world's confidence in ISO-certified contractors. Additionally, partnerships with out-of-region contractors are needed to gain experience in large projects, improve the quality of human resources through training, and conduct evaluations and comparisons of various projects to achieve more accurate results from the ISO 9001:2015-based quality implementation model.